Contribution of Madrassa Education to Sciences, Social Sciences, Literature and to the Society - Alam, Md. Badre (International Journal of Psychosocial Rehabilitation, 2019)
The origin of Madrasa goes back to the time at which the Prophet Mohammad (Peace be upon him) established the first Madrasa in his mosque (Masjid al Nabawi in Madina), with dedicated learners called Asḥāb al- ṣuffah. Starting from Masjid al Nabawi of Madina Al Munawwara, the Madrasa steadily developed throughNizamia; Zaituna, Tunisia,BaithulHikma, Iraq, Al Qaraviyin, Morocco, Al Azhar, Cairo, Madrasa Nizamia, Baghdad, Jami 'ul-Andulus, Spain. The Madrasa education system in India is also very old and unique. It was started with the advent of Muslim rule during the medieval period, when Madrasas were the most prominent centres of learning. During every Muslim regime in India, a separate group of scholars was appointed to look after those madrassas. During British rule, the entire system of education was changed. This gave a serious reminder to the traditional educational set-up. Now present article focuses on the Madrassa education system during British period and post British period and its contribution to science, social science, literature and to the society.